Analisis penggunaan media diorama bagi siswa kelas V di MI Miftahul Ulum Batu untuk menarik minat belajar pada mata pelajaran IPS - Widayanti, Rena (Maliki Interdisciplinary Journal, 2024)
This aim of this researh is to determine the results of the Analysis using Diorama Media for Class V Students at MI Miftahul Ulum Batu to Attract Interest in Studying Social science Subjects. The use of learning media is needed to create a fun learning atmosphere for students. By using learning media, students have a high interest in learning in following the learning process carried out. One of the learning media that can be used in the learning process is the Diorama media.By using this media it is hoped that students can get a attractive learning experience and can master social science subjects well. Because it is very important to use learning media in the learning process, based on the results of research on the use of Diorama media in class V MI Miftahul Ulum it can attract students' interest in learning social science subjects. The research method used in this research is descriptive qualitative, trough interview and observation collection techniques.The need to use learning media requires a teacher who is ready to create innovations in the learning process. The results of this study indicate that the use of Diorama media for fifth grade students of MI Miftahul Ulum can attract students' interest in studying social studies subjects.